Effect of a Recombinant Human Basic Fibroblast Growth Factor 2 (rhFGF-2)-Impregnated Atelocollagen Sponge on Vertical Guided Bone Regeneration in a Rat Calvarial Model - Keisuke Kogure; Akira Hasuike; Risa Kurachi; Yasuyuki Igarashi; Masataka Idesawa; Shuichi Sato (Dentistry Journal)
Background/Objectives: Achieving a sufficient volume of augmented bone, particularly for vertical bone regeneration, remains challenging. This study investigated the use of basic fibroblast growth factor 2 (FGF-2) to promote bone augmentation beyond the skeletal envelope in the rat calvarium. Methods: Seven rats were included in the study, with bilateral experimental sites in the calvarium. Two plastic caps were placed in the calvarium, containing either 0.3% FGF-2 with an atelocollagen sponge or an atelocollagen sponge alone as a control. Bone augmentation within the plastic caps was evaluated using micro-computed tomography (micro-CT) scans and histological sections. Micro-CT measurements, including bone volume measurements, were obtained at 1 week to 12 weeks after surgery. At 12 weeks, the area and height of the newly formed bone were evaluated using histological sections. Results: Starting at 8 weeks after surgery, the volume of the newly formed bone in the 0.3% FGF-2 group was significantly greater than that in the control group. At 12 weeks, histomorphometric analyses revealed that the area and height of the newly augmented bone were 35.6% and 41.9%, respectively, in the FGF-2 group, compared with 9.1% and 13.4%, respectively, in the control group. Conclusions: The inclusion of 0.3% FGF-2 in atelocollagen sponge enhanced vertical bone augmentation beyond the skeletal envelope in the rat calvarium. These findings have potential applications for improving bone regeneration outcomes in dental implant procedures.